Ectopic burst induced by blockade of axonal potassium channels on the mouse hippocampal mossy fiber - Kamiya, Haruyuki (Frontiers in Cellular Neuroscience, 2024)
A potassium channel blocker 4-AP has been shown to exert pronounced convulsive action to generate burst firings when applied to hippocampal slices. However, it remains unclear how the blockade of potassium channels leads to the generation of burst firings. One possibility is ectopic spiking from the sites different from those for physiological spike initiation at the axon initial segment, as suggested for several experimental models of epileptogenesis in vitro. To test for possible ectopic spiking at the distal axon by 4-AP application, direct recordings from large mossy fiber terminals were made with the loose-patch clamp technique in mouse hippocampal slices. To localize the action of 4-AP on the distal axon, focal perfusion, as well as micro-cut to disconnect soma and distal axons, were adopted. Focal application of 4-AP on the distal portion of mossy fibers reliably induced burst discharges of the mossy fiber terminals. Photochemical blockade of potassium channels at distal axons, by the application of RuBi-4-AP, a visible wavelength blue light-sensitive caged compound, and the illumination of blue light caused robust bursting activity originating from distal axons. Computer simulation suggested that local blockade of axonal potassium channels prolongs the duration of action potentials and thereby causes reverberating spiking activities at distal axons and subsequent antidromic propagation towards the soma. Taken together, it was suggested that local blockade of voltage-dependent potassium channels in distal axons by application of 4-AP is sufficient to cause a hyperexcitable state of hippocampal mossy fiber axons.